First record of the genus Troglocollops (Coleoptera, Malachiidae) from China, with description of a new species - Tong, Junbo; Tshernyshev, Sergei E.; Liu, Haoyu; Yang, Yuxia (Zootaxa)
The genus Troglocollops Wittmer, 1965 is reported from China for the first time. A new species is described and illustrated under the name Troglocollops (Troglocollopsoides) sinicus Tong & Yang, sp. nov. from Xinjiang, China. This new species can be easily distinguished from other species of Troglocollops by the body coloration (pronotum yellow with a black longitudinal stripe in the middle, elytra black with blue metallic lustre and yellow margination of apices), antennomere 1 somewhat smaller than 3, and endophallus with five strong spines and two groups of small spines near apex. An identification key to all known species of Troglocollops is updated.